2021
DOI: 10.1177/08850666211055058
|View full text |Cite
|
Sign up to set email alerts
|

Improving Care in Neonatal Intensive Units During the COVID-19 Pandemic: A Survey on Electronic Health Communication

Abstract: Background A novel virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) started spreading through Italy and the world from February 2020, and the pandemic threatened the family-centred care (FCC) model used in the neonatal intensive care unit (NICU). Teleconferences and video calls were employed to keep parents in contact with their babies. This study aimed to evaluate satisfaction and stress levels between parents in the telematic family-centred care group (T-FCC) versus the FCC group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Also, staff’s moral distress, fear for their personal and family safety might have changed the priorities of the NICU staff [ 42 ]. However, recent studies have shown how the provision of FCC could be maintained and improved even during the COVID-19 restrictions, also using mobile technology [ 37 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, staff’s moral distress, fear for their personal and family safety might have changed the priorities of the NICU staff [ 42 ]. However, recent studies have shown how the provision of FCC could be maintained and improved even during the COVID-19 restrictions, also using mobile technology [ 37 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The “no visitors” policy in NICUs during the COVID-19 pandemic causes a great deal of stress and anxiety. Many neonatal clinics around the world have introduced restrictive policies to prevent the spread of the coronavirus, causing parents to experience a great deal of stress, anxiety, and depression ( Bembich et al, 2021 ; Bua et al, 2021 ; Cameron et al, 2020 ; Giuseppe et al, 2021 ; Manuela et al, 2021 ; McCulloch et al, 2021 ; Van Veenendaal et al, 2021 ). Our participants also reported sadness, unhappiness, and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they used to encourage parents to participate in care and promote breastfeeding and skin-to-skin contact. However, they have stopped involving parents in care since the onset of the pandemic, which is likely to put parents in a stressful position ( Giuseppe et al, 2021 ; Konukbay & Arslan, 2011 ; Küçükoğlu et al, 2015 ; Mannering et al, 2021 ; Verderber et al, 2021 ). More research is warranted to better understand the impact of restrictive policies on parent-baby attachment.…”
Section: Discussionmentioning
confidence: 99%
“…In one unit in Italy [ 37 ], NICU parents were updated through a daily video call via smartphones and received information from the physicians about the clinical course of their babies in the presence of a psychologist able to provide support to the families. Parents could see their babies during the video calls, and these were made when the infants were sleeping or feeding, or during procedures.…”
Section: Discussionmentioning
confidence: 99%